Ministry of Trade, Industry and Investment Decree No. 289 of the Year 2014 On Continuing Levying an Export Duty on the Exports of Nitrogen Fertilizers = - Egypt (2025)

(untitled)
Ministry of trade, industry and investment decree no. 189 of the year 2014 on continuing levying an export duty on the exports of nitrogen fertilizers – ministry of agriculture and land reclamation ministerial decree no. 764 of the year 2013 وزارة التجارة النصاعة والاستثمار قرار رقم 289 لسنة 2014 فى شأن استمرار فرض رسم صادر على الصادرات من الاسمدة الآزوتية – وزارة الزراعة واستصلاح الاراضى قرار وزارى رقم 764 لسنة 2013